Lower limb soft tissue reconstruction using free ALT flaps: multimodal parameter analysis to predict the level of spontaneous reinnervation. Issue 1 (28th February 2023) - Watfa, William; Sapino, Gianluca; Teatini, Francesco; Oranges, Carlo M.; Cherubino, Mario; Guiller, David; Raffoul, Wassim; di Summa, Pietro G.
Abstract: Introduction: This work aims to assess lower limb free flaps spontaneous sensory recovery by comparing and analyzing a single standardized reconstructive procedure, namely the free noninnervated anterolateral thigh (ALT) flap in order to evaluate which flap or patient-related factors may predict flap reinnervation. Methods: Between January 2010 and March 2018 all nonreinnervated ALT flaps for lower limb coverage performed at our institution were screened. We excluded from the study flaps with less than 18 months of follow-up time, neurotized flaps, and those from patients who missed the last follow up. Sensory modalities that were evaluated included the two-point discrimination (2PD) test, measured in mm; and the Semmes–Weinstein monofilament (SWM) test, measured in gram. The sensory parameter results were compared and analyzed according to flap size (two groups; <160 cm 2 vs. > 160 cm 2 ), and post-op time of testing (two groups; <18–28 months vs. > 28 months). Results: Twenty-one ALT free flaps were finally retained by this study. Our findings showed that flaps of smaller surface area showed a significantly better return in sensory discrimination 2PD and in sensory cutaneous pressure perception SWM testing. Conclusion: This work establishes for the first time some key quantitative data that can help predict free flap spontaneous reinnervation outcomes when using the same ALT flap. In our series, flaps surface remains the main discriminant value for a better sensory recovery.